EFFECT OF DIFFERENT HERBICIDES ON GROWTH AND EFFICACY FOR WEED CONTROL IN ONION (ALLIUM CEPA L.) SEED CROP - Kumar, NARESH; MOURYA, I.B. (Annals of Agricultural Research, 2014)
An exerpiment was conducted to study the comparative efficacy of fluchioralin, pendimethalin andoxyflurofen applied alone and along with hand weeding at 45 days after planting (DAP), 3 handweeding alone given 20, 40 and 60 days after planting (DAP) and unweeded check were carried out.It was concluded that pendimethalin @ 1.0 kg / ha along with a hoeing and weeding at 45 days afterplanting (DAP) was found most effective and economically viable weed control treatment for onionseed production.